SOME PECULIARITES OF THE ADVERSARIAL PRINCIPLE IN THE CIVIL PROCEDURAL RELATIONS - Arkhoshashvili, Leila (European Scientific Journal, ESJ, 2012)
This article concerns the actual problems of the Civil Procedural Law – the adversarial principle in the civil procedural relations. Each person has the right to protect his/her infringed rights in court. In accordance with the first part of the Article 4 of the Civil Procedural Code of Georgia legal proceedings shall be exercised on the basis of the adversarial principle. The Article underlines the second part of the Article 4 according to which the court may apply the measures provided under this Code on its own initiation. In the author’s opinion, this stipulation contradicts the nature of competition. The article expresses the idea that the court should not be actively involved in gathering evidences; it must support the parties if they cannot obtain the evidence by themselves for some reason and submit a petition to the court. The court’s role is regulated differently with respect to the adversarial principle in legislations of different countries. However, the Common Law regards the trial as a kind of tournament where a judge plays a role of an arbiter. Each party shall provide the evidence.